Vertical gust velocities and variations in normal g associated With clear air turbulence and turbulence in cumulus clouds As studied from ‘ESE data’ (MAUSAM, 1978)
'Exercise Storm Exchange' (ESE) is a name given to the Project in which an RAF Cauberra-aircraft PR7/9 was lent to India for undertaking atmospheric studies. The aircraft was flown in India during June to September 1972 from Bangalore, Pune, Calcutta and Agra, to study the synoptic and meso-soale systems in the summer monsoon circulation over India.This paper deals with the analysis of the data on variations in normal gravity (g) and vertical gusts (Vg) encountered by the aircraft in two different conditions – (1) in clear air while it was flying at different levels in the upper troposphere between Bangalore and Trivandrum in July 1972 and (2) while it was flying through growing cumulus clouds in the vicinity of Bangalore on 20 September 1972. Using the data extracted at 0.1 second intervals, the vertical gust velocity and the variations in normal gravity were evaluated and this data has been analysed. The analysis showed only light or moderate turbulence in the fast easterly field between 20000 and 50000 ft over Peninsular India. Moderate to severe turbulent conditions were encountered while probing the cumulus clouds. The maximum gust velocity in the former case was 17.5 ft per sec and in the later case 32.5 ft per sec.